Implementation of a heart failure educational intervention for patients with recent admissions for acute decompensated heart failure - Stahlman, Sarah; Huizar-Garcia, Stephanie; Lipscomb, Justina; Frei, Christopher; Oliver, Ashley (Frontiers in Cardiovascular Medicine, 2023)
Purpose This study examined whether implementation of a heart failure (HF) education class targeted at patients and their caregivers decreased worsening HF, emergency department (ED) visits and hospital admissions, and improved patient quality of life and confidence in disease state management. Methods Patients with HF and a recent hospital admission for acute decompensated heart failure (ADHF) were offered an educational course covering HF pathophysiology, medications, diet, and lifestyle modifications. Patients completed surveys before and 30 days after completion of the educational course. Outcomes of participants at 30 and 90 days after class completion were compared against outcomes for the same patients at 30 and 90 days prior to course attendance. Data was collected using electronic medical records, in-person during the class, and during a phone follow-up. Results The primary outcome was a composite of hospital admission, ED visit, and/or outpatient visit for HF at 90 days. A total of twenty-six patients attended classes between September 2018 and February 2019 and were included in the analysis. Median age was 70 years, and most patients were white. All patients were American College of Cardiology/American Heart Association (ACC/AHA) Stage C and a majority had New York Heart Association (NYHA) Class II or III symptoms. Median left ventricular ejection fraction (LVEF) was 40%. The primary composite outcome occurred significantly more frequently in the 90 days prior to class attendance than in the 90 days following attendance (96% vs. 35%, p < 0.01). Likewise, the secondary composite outcome occurred significantly more frequently in the 30 days before class attendance than in the 30 days following (54% vs. 19%, p = 0.02). These results were driven by a decrease in admissions and ED visits for HF symptoms. Survey scores related to patient HF self-management practices and patient confidence in ability to self-manage HF increased numerically from baseline to 30 days after class attendance. Conclusion Implementation of an educational class for HF patients improved patient outcomes, confidence, and ability to self-manage HF. Hospital admissions and ED visits also decreased. Adoption of such a course might help to decrease overall health care costs and improve patient quality of life.